Potentialities of MSMEs in Nepal and the Ways Forward to Unlock - Acharya, Govinda Prasad (SADGAMAYA, 2025)
MSMEs are pivotal in the broader economic perspectives of nations. The cases of developing economies are even more vivid. Promoting entrepreneurial competency and generating employment remain the primary attractiveness of MSMEs worldwide. This article focuses on how countries assess and transform this vivacity as an engine for nations' social and economic growth. In this context, the author attempts to present ground scenarios of such enterprises in Nepal precisely and the SAARC member nations in general. The analysis and inferences drawn concerning potentialities, challenges, and ways to achieve economic benefits and human development are implicitly based on reviews of scholarly articles and research reports from professional entities. The article is assumed to critically explore previously unexplored areas that could serve as a reservoir for the nation's social and economic well-being. The article also opens the path for policymakers and planners to retain outgoing youths and employ their vigor and innovation for national prosperity.